Development of Animated Video Media to Improve Elementary School Students’ Learning Comprehension - Bidari, Berliana Safa; Prihatin, Relly; Devayanti, Karismaya (Indonesian Journal of Learning and Instructional Innovation, 2026)
This research is motivated by the lack of variety in the use of learning media in the subject of science and science on the topic of force in grade IV elementary school. The learning process is still dominated by lecture methods and the use of textbooks so that students are less active and have difficulty in understanding abstract material. Therefore, interesting and interactive learning media are needed to help students understand the material more easily. This research aims to: (1) develop Animaker-based animated video media on the topic of force for grade IV elementary school students, and (2) determine the level of feasibility of Animaker-based animated video media based on validation by material experts and media experts. This research is a research and development (R&D) using the ADDIE model limited to the analysis, design, and development stages. The analysis stage is conducted through observation, interviews, and learning needs analysis. The design stage includes the preparation of storyboards, materials, visual displays, and research instruments. The development stage is carried out by creating animated video media using the Animaker application and conducting media validation by material experts and media experts. Data collection techniques used observation, interviews, and validation questionnaires. The data obtained were analyzed using quantitative and qualitative descriptive analysis. The research results show that the Animaker-based animated video media for the topic of style was categorized as "Very Good" based on validation by material experts and media experts. The developed media was deemed appropriate for the learning outcomes and characteristics of elementary school students, and featured engaging visuals, audio, and animation. Animaker-based animated video media also helped students understand the topic of style more concretely and created a more active and enjoyable learning environment. Based on the research results, it can be concluded that the Animaker-based animated video media for style is suitable for use as a learning medium for fourth-grade elementary school science.